Crisis, salud y calidad de vida. Algunas evidencias en España y Portugal - Elena Cachón González (e-cadernos ces)
Both the impact of the crisis unleashed in 2008 and its management through austerity policies have had a clear effect on health and health services both in Spain and in Portugal. Some evidences of this impact are analyzed in this article from a dual perspective: the objective indicators related to health and health services in both countries, and the subjective indicators on quality of life related to health and health services, including the users’ satisfaction with the health services. The data shows that, although the objective indicators have improved once the crisis was overcome, that was not the case with the subjective indicators. This happens, among other reasons, because the social determinants of health are still far from overcoming the crisis.